2009
DOI: 10.1039/b810256b
|View full text |Cite
|
Sign up to set email alerts
|

Micropumps operated by swelling and shrinking of temperature-sensitive hydrogels

Abstract: This paper describes two types of polymeric micropumps based on the temperature-sensitive hydrogel poly(N-isopropylacrylamide). The gel actuators are realised as photopolymerised patterns and microgels. They are electrothermically controlled by resistive heating elements. The diffusion-based micropump contains a photopatterned monolithic actuator, which is placed within the pump chamber, and provides a valveless single layer set-up. The diffusion micropump is intended for low performance applications and can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 38 publications
1
80
0
1
Order By: Relevance
“…In technical applications, hydrogels serve as basic building blocks for gel electrophoresis or size exclusion chromatography, etc. Moreover they are nowadays implementet as "intelligent" chemo-mechanical materials using them as stimuli-responsive sensor-actor systems [1] based on their high sensitivity to environmental conditions [2] such as pH [3,4], temperature [5], solvent composition [3], light or pressure [2]. In biological contexts, hydrogels have become ideal model systems for tissue matrices due to their similarity to the extra-cellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…In technical applications, hydrogels serve as basic building blocks for gel electrophoresis or size exclusion chromatography, etc. Moreover they are nowadays implementet as "intelligent" chemo-mechanical materials using them as stimuli-responsive sensor-actor systems [1] based on their high sensitivity to environmental conditions [2] such as pH [3,4], temperature [5], solvent composition [3], light or pressure [2]. In biological contexts, hydrogels have become ideal model systems for tissue matrices due to their similarity to the extra-cellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For these purposes, various actuation principles have been adopted including electrostatic, 2,3,6 thermal 4,14 or piezoelectric. 1,7 However, these methods present diverse limitations, making difficult their direct utilization in the final devices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be easily integrated on lab-on-a-chip devices. (Richter et al, 2009) Nestler and co-workers reported a micropump chip that employed a hydrogel based on poly(acrylic acid) sodium salt (PAAS) for generating gas molecules by electrolysis. As almost no heat is generated by electrolysis, this pumping principle is well suited for proteinsensing applications.…”
Section: Micropumps and Micromixersmentioning
confidence: 99%